What Determines Students’ Performance in Introductory Accounting Classes? A Mixed Method - Sartini Wardiwiyono; Sumaryanto Sumaryanto (Universitas Ahmad Dahlan, 2022)
This study investigated factors determining students' performance in the Introductory Accounting classes. It was carried out using a mixed-method approach. Three research hypotheses based on the results of prior studies were tested using regression analysis. Additionally, a qualitative approach using thematic analysis was used to identify factors influencing students' performance. The study involved 90 students who were selected using the purposive sampling method. Secondary data related to those students were gathered through a documentation procedure, whereas primary data were obtained through interviews and observation involving those sample students. The results of the quantitative analysis showed that motivation had a positive impact on students' performance in Introductory Accounting classes. It was also observed that female students had better performance than male students. However, this study did not find accounting educational background as a significant variable in determining students' performance. For the thematic analysis, the study observed nine factors influencing the students' performance in Introductory Accounting classes. Those factors were related to lecturers, learning method, classroom, family background, references, assignments, tutor, and group study. This study contributes to the upward literature in accounting education. It also provides an insight for the Accounting Study Program in higher education institutions in designing accounting curricula, for lecturers in designing learning processes, and for accounting students in understanding the determinants of their performance.